EU effect: Exporting emission standards for vehicles through the global market economy. (1st December 2016) - Crippa, M.; Janssens-Maenhout, G.; Guizzardi, D.; Galmarini, S.
Abstract: Emission data from EDGAR (Emissions Database for Global Atmospheric Research), rather than economic data, are used to estimate the effect of policies and of the global exports of policy-regulated goods, such as vehicles, on global emissions. The results clearly show that the adoption of emission standards for the road transport sector in the two main global markets (Europe and North America) has led to the global proliferation of emission-regulated vehicles through exports, regardless the domestic regulation in the country of destination. It is in fact more economically convenient for vehicle manufacturers to produce and sell a standard product to the widest possible market and in the greatest possible amounts. The EU effect (European Union effect) is introduced as a global counterpart to the California effect . The former is a direct consequence of the penetration of the EURO standards in the global markets by European and Japanese manufacturers, which effectively export the standard worldwide. We analyze the effect on PM2.5 emissions by comparing a scenario of non-EURO standards against the current estimates provided by EDGAR. We find that PM2.5 emissions were reduced by more than 60% since the 1990s worldwide. Similar investigations on other pollutants confirm the hypothesis that the combined effect of technological regulations and their diffusion through global markets can also produce a positive effect on the global environment. While we acknowledge the positive feedback, we also demonstrate that current efforts and standards will be totally insufficient should the passenger car fleets in emerging markets reach Western per capita figures. If emerging countries reach the per capita vehicle number of the USA and Europe under current technological conditions, then the world will suffer pre-1990 emission levels. Highlights: The "EU effect" is defined as counterpart to the California effect at global scale. EURO standards reach the global market in spite of presence of local regulation. EU and US vehicle emission standards reduced global PM2.5 road emissions of 60%. Actual standards are insufficient should CHN and IND vehicle fleets equal US/EU ones.